Does the Genitive Operate in the Hungarian Case System?: II. The Ø-/nak-/nek-Genitive - Bielecki, Robert (Lingua Posnaniensis, 2011)
The present paper should be regarded as a direct continuation of the article Does the Genitive Operate in the Hungarian Case System? I. The é-Genitive. The core of the adopted approach represents the standpoint that present-day Hungarian cannot be conceived as a language exempt from any case syncretism. The possibility of distinguishing different case categories relevant for this language by referring only to the form of their markers (endings) is illusory. What is more, it creates a space where some phenomena remain imperceptible. The postulated attributive genitive category can be distinguished not only on the basis of its syntactic properties. The manifestations of this case also differ substantially from the manifestations of other recognized cases. It is difficult to regard the attributive genitive in Hungarian as syncretic with nominative or dative in the sense known in general linguistics, because the appropriate markers turn out to be insufficient in semifying (marking grammatically) the required meaning. They must be complemented by other markers attached to the head of the attributive syntagm (a diák/Ø könyv/e, a diák/nak a könyv/e ‘the student's book’). The properties of the distribution of the Hungarian attributive genitive with its two main manifestations (the endingless one: a diák könyve, and with ending: a diáknak a könyve) can be regarded as a contribution to the general theory of syntax; the genitive attributes of different grades are marked there substantially (a diák/Ø (III) könyv/e (II) cím/é/nek (I) a fordítás/a ‘the translation of the title (I) of the book (II) of the student (III)’) and not only by their linear order as in many Indo-European and Finno-Ugric languages. When the word fulfilling the attributive function belongs to the category of personal pronoun, concord can be identified between it and its head in person and number (az én könyv/em ‘my book, the book of mine’). The factual elision of personal pronouns resulting from their redundancy in this context gives no grounds to state that morphemes like -em in a könyv/em do not fulfil any syntagmatic function. Such an utterance constitutes a discrepancy with the analogous behaviour of personal pronouns in relation to finite verbal forms (olvas/ok ‘I read’ → olvas/ok ‘(I) read’) where no-one speaks of the irrelevancy of the personal endings in reference to their syntagmatic function. The necessity of distinguishing of socalled "marks" (here "possessor marks") is being questioned here; those morphemes are not deprived of fulfilling the syntagmatic function ascribed traditionally to the case endings in the case of nominal flexion. They are regarded here as parts of the discontinuative (genitive) case markers. The specific features of the Hungarian genitive include its sharp division into two subcategories: (i) the é-genitive and (ii) the Ø-/nak-/nek-genitive. Their complementary distribution, together with other discussed properties, additionally corroborates the relevance of distinguishing for them a common upper morphosyntactic category called the genitive case. And finally, Hungarian turns out to be a language where the accumulation of multiple case meanings, all being manifested substantially within the boundaries of one word, can be attested (a diák/om/é/é/t ‘the one of the one of my student’).